Spur Pruning Leaving One Bud is an Interesting Viticultural Strategy to Control Bud Acrotony in Bolivian Vineyards - Gutiérrez-Gamboa, G.; Pinedo , X.; Villena, W.; Araya-Alman, M.; Pszczólkowski, P. (South African Journal of Enology and Viticulture, 2023)
Bolivian viticulture is mostly found in the Central Valley of Tarija, which is characterised by a subtropical climate with high thermal oscillation in winter that results in low accumulation of chilling units. Such climatic conditions accentuate acrotony in vines, which affect budburst uniformity and, consequently, yield and bunch quality at harvest. The aim of this study was to evaluate the effect of different spur pruning strategies on the percentage of budburst and fertility of buds located in different nodal positions in both wine and table grape varieties growing in the Central Valley of Tarija. The results show that allocating spurs with fewer buds improved the budding of most of the distal buds studied. This was noted in both the wine and table grape cultivars, but mostly in the latter. Spur pruning leaving one bud improved the percentage of budburst and the fertility of the distal buds in Cabernet Sauvignon, Cardinal and Ribier, thereby preventing bud acrotony, compared to spur pruning leaving two buds. Spur pruning leaving two buds improved the budburst of latent buds in Cabernet Sauvignon. Therefore, to avoid acrotony patterns, viticulturists should perform pruning leaving one bud.